Marginal Gap of Milled versus Cast Gold Restorations. Issue 1 (4th February 2016) - Johnson, Russell; Verrett, Ronald; Haney, Stephan; Mansueto, Michael; Challa, Suman
Abstract: Purpose: This in vitro study evaluated and compared the vertical marginal gap of cast and milled full coverage gold copings using two margin designs (chamfer and chamfer bevel) before and after fitting adjustments. Materials and Methods: Ten impressions were made of two metal master dies (one chamfer margin, one chamfer‐bevel margin) and poured twice in Type IV stone. The 20 subsequent casts with 40 dies were split into four groups (n = 10); cast gold bevel, cast gold chamfer, milled gold bevel, and milled gold chamfer groups. The cast specimens received approximately 40 μm die relief no closer than 1 mm from the finish line. Cast copings were hand waxed, cast in a high noble gold alloy, chemically divested, and the sprues were removed. For milled gold copings, casts were scanned and copings designed using 3shape D900 scanner and software. Parameters were set to approximate analog fabrication (cement gap = 0.01 mm; extra cement gap = 0.04 mm, drill radius = 0.65 mm). Copings were milled from the same high noble alloy. All copings were seated on their respective master die in a custom scanning jig and measured using a measuring microscope at 90× (60 measurements per specimen, 15 per surface). Following initial measurements, all copings were adjusted on stone dies. The number of adjustment cycles was recorded and post‐adjustment measurements were made using the same method. Data were analyzed using independent and paired t ‐tests. Results: Milled gold copings with a beveled margin (11.7 ± 20.4 μm) had a significantly ( p < 0.05) smaller marginal gap than cast gold copings with a beveled margin (43.6 ± 46.8 μm) after adjustment. Cast gold copings with a chamfer margin (22.7 ± 24.7 μm) had a significantly ( p < 0.05) smaller marginal gap than milled gold copings with a chamfer margin (27.9 ± 31.6 μm) following adjustments. Adjustments significantly decreased marginal gap for both cast groups ( p < 0.05) and the milled chamfer bevel group ( p < 0.05) but had no significant effect on the milled chamfer group. Conclusions: Within the limitations of this study, results indicate that gold restorations milled with the tested parameters provide a vertical marginal gap that is an acceptable alternative to traditional gold crown casting techniques.